A Novel Advanced Gauge Reader System Based on M-Bus Technology - Jing-Min Wang; Thomas Chen; Shieh-Shing Lin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Applications in the signal processing technology corresponding to various gauges have been widely popularized exploration. However, there is rarely proposed corresponding to how to employ gauge reader with lower cost but longer distance. M-Bus (Meter-Bus) is an inexpensive solution for widespread networking and remote meter reading for the consumption data collection. This work based on the M-Bus technology presented a novel signal processing technology of Advanced Gauge Reader System (AGRS). In particular, this paper also implemented the proposed device for real applications. The proposed AGRS is a cost-effective, stable and reliable remote water meter reading system. Numerous simulations and tests have been made to demonstrate the efficiency of this work. The empirical findings may provide some valuable references for the related applications. DOI : http://dx.doi.org/10.11591/telkomnika.v12i2.3794